Comparison of apically extruded debris after large apical preparations by full‐sequence rotary and single‐file reciprocating systems. (29th July 2015) - Silva, E. J. N. L.; Carapiá, M. F.; Lopes, R. M.; Belladonna, F. G.; Senna, P. M.; Souza, E. M.; De‐Deus, G.
Abstract: Aim: To evaluate the amount of apically extruded debris produced by ProTaper Universal (PTU), ProTaper Next (PTN), WaveOne (WO) and Reciproc (R) systems after large apical preparations. Methodology: Sixty mandibular premolars with a single canal were selected and randomly assigned into 4 groups ( n  = 15) according to the system used for root canal preparation: PTU, PTN, WO and R groups. Canal preparations were performed up to size 40 in each group. Distilled water was used as an irrigant, and the apically extruded debris from each tooth was collected in pre‐weighted glass vials and dried. The average weight of debris was assessed using a microbalance, and the data were analysed statistically using one‐way analysis of variance and the post hoc Tukey multiple comparison test (α = 0.05). Results: The PTU system was associated with significantly more debris than the other systems ( P  <   0.05). No significant differences were found between PTN, WO and R systems ( P  >   0.05). Conclusions: All systems were associated with apical debris extrusion when canals were prepared to a large apical size. The PTU system was associated with more debris extrusion.